QUANTITATIVE EVALUATION OF MASSIVE SULFIDE ORE FORMATION - Kontar E.S. (My University, 2002)
Data on 313 massive sulfide ore districts, ore fields, and individual deposits dated from the Late Archean to the present day, referred to those of Cyprus-, Urals-, Kuroko-, and Filizchai-type, and situated on all of the continents have been considered. Data on copper, zinc, and lead distribution patterns in deposits of different types were generalized for deposits of various geological ages and metallogenic provinces. Most of the massive sulfide deposits, reserves of ores, copper, zinc, and lead are shown to have been formed in Precambrian, i.e., before the existence of Pangea. The distribution of total reserves of massive sulfide ores deposited during geological epochs between deposits of different types was evaluated. Smirnov's idea on the conservatism of the massive sulfide metallogeny was proven.